The relationship between transport, economic growth and environmental degradation for ninety countries - Listiono, Listiono (Sustinere: Journal of Environment and Sustainability, 2018)
This paper investigates the relationship between freight transport, economic growth and environmental degradation (CO2 emissions) experienced by ninety countries over the period 1980-2014. The estimation is divided into the global panel, high-income countries, upper-middle income countries, lower-middle income countries, and lower-income countries. This paper employed simultaneous equation Model and was estimated by Three-Stage Least Squares (3SLS). The results discovered the existence of bi-directional causality relationship between economic growth and freight transport in the high-income countries and lower-income countries. The result also indicated the bi-directional causality relationship between the transportation and CO2 emissions in the panel upper-middle-income countries. Lastly, the finding indicated the bi-directional causality between economic growth and CO2 emissions in lower-middle income countries.